Predicting colorectal cancer risk: a novel approach using anemia and blood test markers - Zhang, Zhongqi; Zhang, Tianmiao; Zhang, Rongcheng; Zhu, Xiaonian; Wu, Xiaoyan; Tan, Shengkui; Jian, Zhiyuan (Frontiers in Oncology, 2024)
Background and objectives: Colorectal cancer remains an important public health problem in the context of the COVID-19 (Corona virus disease 2019) pandemic. The decline in detection rates and delayed diagnosis of the disease necessitate the exploration of novel approaches to identify individuals with a heightened risk of developing colorectal cancer. The study aids clinicians in the rational allocation and utilization of healthcare resources, thereby benefiting patients, physicians, and the healthcare system. Methods: The present study retrospectively analyzed the clinical data of colorectal cancer cases diagnosed at the